2023
DOI: 10.3389/fpain.2023.1216190
|View full text |Cite
|
Sign up to set email alerts
|

Allogenic platelet-rich plasma for treatment of knee and hip osteoarthritis

Abstract: Osteoarthritis (OA) induces tremendous amounts of stress and financial burden on patients and healthcare systems worldwide. Current treatments have limitations and do not address the etiopathogenetic cause of OA. Regenerative medicine may circumvent limitations posed by traditional modalities and relies on the utilization of biologics including platelet-rich plasma (PRP). Several peer-reviewed studies have documented the safety and efficacy of autologous PRP in mitigating symptoms in knee and hip OA patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…There has been considerable interest in the use of biologics, including platelet-rich plasma (PRP) for musculoskeletal regenerative medicine applications [ 9 ]. Several studies, including systematic reviews and meta-analyses, randomized controlled trials, case studies and reports, etc.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There has been considerable interest in the use of biologics, including platelet-rich plasma (PRP) for musculoskeletal regenerative medicine applications [ 9 ]. Several studies, including systematic reviews and meta-analyses, randomized controlled trials, case studies and reports, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies, including systematic reviews and meta-analyses, randomized controlled trials, case studies and reports, etc. have shown the safety and efficacy of PRP [ 9 ]. In contrast, the subpar outcomes associated with a lack of standardization and characterization of PRP preparations, and patient-related variables including age, comorbidities, mental and physical stress levels, alcohol consumption, smoking status, concomitant medication, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent systematic review and meta-analysis assessed 24 randomized controlled trials (RCTs) with 1,344 patients and reported significant improvements in several patient-reported outcome measures (PROMs) including visual analog scale (VAS), knee injury and osteoarthritis outcome score (KOOS), Western Ontario and McMaster Universities Arthritis Index (WOMAC), and International Knee Documentation Committee (IKDC) scores in the PRP group compared to the saline and HA [ 4 ]. Nevertheless, the efficacy of PRP remains controversial and is ascribed to a lack of standardized formulation protocol, inter- and intra-patient variables, and so on [ 5 ]. Autologous protein solution (APS) is formulated by exposing leukocyte-rich PRP to polyacrylamide beads, to obtain higher levels of growth factors and anti-inflammatory cytokines and lower levels of pro-inflammatory cytokines, thereby compound the anabolic effects of PRP with autologous anti-inflammatory homeostatic characteristics [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The lack of standardized formulation protocols and patient variables, including age, https://doi.org/10.18231/j.ijor.2023.022 2581-8112/© 2023 Author(s), Published by Innovative Publication. 115comorbidities, concomitant medications taken, etc., have been attributed to subpar outcomes associated with studies utilizing orthobiologics, and all of this information is critical to ensure repeatability and reproducibility of studies outcomes [8][9][10]. …”
mentioning
confidence: 99%